2001
DOI: 10.1530/eje.0.1440401
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical screening for subclinical cortisol-secreting adenomas amongst adrenal incidentalomas

Abstract: Objective: Biochemistry and 131 I-6b-iodomethyl norcholesterol scintigraphy (IMS) have both been used to assess cortisol secretion by adrenocortical incidentalomas. However, which biochemical abnormalities indicate subclinical corticoid excess is still debatable whilst IMS is expensive and cumbersome. The aim of the study was to evaluate prospectively patients with adrenal incidentalomas using both IMS and biochemical methods to examine whether the IMS pattern is associated with biochemical abnormalities and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 40 publications
5
62
0
2
Order By: Relevance
“…Bardet et al (1996) found that low 8 am dehydroepiandrosterone sulfate, low 8 am ACTH, basal urinary free cortisol, unsuppressed 8 am serum cortisol after overnight 1 mg dexamethasone suppression, unsuppressed day 2 serum cortisol, and unsuppressed day 2 urinary free cortisol after low-dose dexamethasone suppression had low sensitivity (0-50%) and moderate specificity (79-94%) to differentiate unilateral from bilateral scintigraphy uptake. In contrast, Valli et al (2001) found that unsuppressed 8 am cortisol after overnight dexamethasone suppression had 100% sensitivity and 67% specificity to predict unilateral uptake. Studies of diagnosis of catecholamine excess and primary hyperaldosteronism reveal similar problems in sensitivity and specificity.…”
Section: Issues In Biochemical Diagnosismentioning
confidence: 83%
“…Bardet et al (1996) found that low 8 am dehydroepiandrosterone sulfate, low 8 am ACTH, basal urinary free cortisol, unsuppressed 8 am serum cortisol after overnight 1 mg dexamethasone suppression, unsuppressed day 2 serum cortisol, and unsuppressed day 2 urinary free cortisol after low-dose dexamethasone suppression had low sensitivity (0-50%) and moderate specificity (79-94%) to differentiate unilateral from bilateral scintigraphy uptake. In contrast, Valli et al (2001) found that unsuppressed 8 am cortisol after overnight dexamethasone suppression had 100% sensitivity and 67% specificity to predict unilateral uptake. Studies of diagnosis of catecholamine excess and primary hyperaldosteronism reveal similar problems in sensitivity and specificity.…”
Section: Issues In Biochemical Diagnosismentioning
confidence: 83%
“…Since adrenal scintiscan may not be available in all centers, the 1 mg overnight dexamethasone suppression test may be a rapid and convenient tool to identify patients at risk for disease progression. With revised cut-off levels for a normal response, this test shows a good correlation with scintigraphic patterns and a high sensitivity in the detection of mild subclinical hypercortisolism (92,93).…”
Section: Analysis Of Risk Factorsmentioning
confidence: 99%
“…As to the role of adrenocortical scintigraphy as a predictive factor for adrenal hyperfunction, findings of an increased risk of adrenal hyperfunction in patients showing exclusive uptake by the adrenal mass indicate that this scintigraphic pattern may represent an early phase of functional autonomy of the adrenal adenomas also in the case of apparently normal hormone function (42,52,67,92,127). Indeed, a mild degree of autonomy is demonstrated by lack of complete suppression after low-dose dexamethasone (92,93).…”
Section: Analysis Of Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the terms subclinical Cushing's syndrome or subclinical autonomous glucocorticoid hypersecretion (SAGH) have been used. 8,9 There is evidence for an increased prevalence of certain of the problems associated with Cushing's syndrome in patients with SAGH, such as increased cardiovascular risk factors (hypertension, central obesity, diabetes, impaired glucose tolerance, hyperlipoproteinaemia) and an increased risk of osteoporosis, supporting the significance of their early recognition and appropriate management. 10,11 …”
Section: Subclinical Autonomous Glucocorticoid Hypersecretionmentioning
confidence: 99%